1997
DOI: 10.1046/j.1365-2125.1997.00615.x
|View full text |Cite
|
Sign up to set email alerts
|

Reports of hypoglycaemia associated with the use of ACE inhibitors and other drugs: a case/non‐case study in the French pharmacovigilance system database

Abstract: Aims To test the existence of an association between reports of hypoglycaemia and angiotensin converting enzyme inhibitors, in a spontaneous reports database. Methods The French Pharmacovigilance database was examined for an association between adverse drug reaction reports mentioning hypoglycaemia, and angiotensin converting enzyme inhibitors (ACEI) using the case/non-case methodology, with reports of hypoglycaemia as cases and all other reports as comparators. The association between ACEI or other chosen dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 124 publications
(72 citation statements)
references
References 4 publications
0
71
0
1
Order By: Relevance
“…Overall hypoglycaemia was associated with the use of ARBs [ROR 2, 95% confidence interval (CI) 1, 3] and with the use of ADAs (ROR 32, 95% CI 27, 37). Moreover, the use of ARBs was associated with the use of ADAs (OR 7, 95% CI 6,8). Considering separately reports with and without ADA, the association of ARB use with a higher risk of hypoglycaemia disappeared (OR 0.4, 95% CI 0.2, 0.8 and OR 2, 95% CI 1, 3, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Overall hypoglycaemia was associated with the use of ARBs [ROR 2, 95% confidence interval (CI) 1, 3] and with the use of ADAs (ROR 32, 95% CI 27, 37). Moreover, the use of ARBs was associated with the use of ADAs (OR 7, 95% CI 6,8). Considering separately reports with and without ADA, the association of ARB use with a higher risk of hypoglycaemia disappeared (OR 0.4, 95% CI 0.2, 0.8 and OR 2, 95% CI 1, 3, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Previous experience with reporting of hypoglycaemia with ACEIs had raised the possibility of confounding by indication [8], at a time when data-mining tools were not generally available. Such signals can now easily be generated by automated methods that are widely used for the detection of new adverse drug reactions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The problems associated with the recruitment of controls for case/control studies do not apply to case/non-case studies, for all reports not identified as cases are non-cases. Several studies using the case/non-case method have been published on this database applying to different fields of drug safety [24][25][26]. One limitation of the pharmacovigilance database and consequently of the case/non-case method [20,26] lies in the selection and notoriety bias due to the spontaneous notification system, which depends on the cooperation and goodwill of healthcare professionals [25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%